Advances in Grid and Pervasive Computing 5th International Conference, GPC 2010, Hualien, Taiwan, May 10-13, 2010. Proceedings - Bellavista, Paolo; Chang, Ruay-Shiung.; Chao, Han-Chieh.; Lin, Shin-Feng.; Sloot, Peter M. A.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the proceedings of the 5th International Conference, CPC 2010 , held in Hualien, Taiwan in May 2010. The 67 full papers are carefully selected from 184 submissions and focus on topics such as cloud and Grid computing, peer-to-peer and pervasive computing, sensor and moile networks, service-oriented computing, resource management and scheduling, Grid and pervasive applications, semantic Grid and ontologies, mobile commerce and services.
Keynote Speeches -- Track 1: Cloud and Grid Computing -- Track 2: Peer-to-Peer and Pervasive Computing -- Track 3: Sensor and Mobile Networks -- Track 4: Service-Oriented Computing -- Track 5: Resource Management and Scheduling -- Track 6: Grid and Pervasive Applications -- Track 7: Semantic Grid and Ontologies -- Track 8: Mobile Commerce and Services -- Track 9: Multimedia Applications for Cloud -- Track 10: Intelligent Network Management.
Keywords: Computer science; Computer Communication Networks; Software engineering; Operating systems (Computers).; Computer software; Information systems; Computer Science; Algorithm Analysis and Problem Complexity; Computer Communication Networks; Information Systems Applications (incl.Internet).; Software Engineering; Operating Systems; Programming Techniques